Clonal Expansion of Mitochondrial DNA Deletions in Multiple Sclerosis - Campbell, Graham R (2012)
OBJECTIVE: Mitochondrial DNA deletions (Δ-mtDNA) are implicated in the pathogenesis of multiple sclerosis (MS), Parkinson’s disease (PD), Alzheimer’s disease (AD) and ageing. Given the diffuse nature of inflammation in MS, aim of this study was to determine whether Δ-mtDNA caused respiratory deficient cells in excess of age within choroid plexus (CP) and ongoing mutagenesis or clonal expansion accounted for the respiratory deficiency in MS. METHODS: Respiratory chain complex IV and complex II activity was determined sequentially using histochemistry. Δ-mtDNA were characterized using real time PCR, long range PCR, sequencing and single molecule PCR. Sources of reactive oxygen and nitrogen species (RONS) were explored using immunohistochemistry. RESULTS: Respiratory deficient cells (lacking complex IV and with intact complex II activity) within CP epithelium were in excess of age in MS, PD and AD. Subunit-I of complex IV was lacking to a greater extent in MS than controls. Percentage of respiratory deficient cells harboring >50% heteroplasmy level of Δ-mtDNA was significantly greater in MS than PD, AD and controls. Long range PCR and sequencing confirmed Δ-mtDNA. Single molecule PCR identified clonally expanded Δ-mtDNA in MS, despite an increase in sources of RONS. INTERPRETATION: Our findings establish clonal expansion of Δ-mtDNA causing respiratory deficiency in MS and the extraparenchymal intracranial location indicated the potential to involve multiple cell types. Understanding factors that influence clonal expansion of Δ-mtDNA, a molecular link between inflammation and delayed cellular energy failure, may identify potential therapeutic targets for progressive forms of MS as well as other neurodegenerative disorders.